2021
DOI: 10.3390/ma14133690
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treatment of Polypropylene (PP) Fiber on the Sulfate Corrosion Resistance of Cement Mortar

Abstract: Sulfate erosion is one of the most complex and harmful chemical corrosion actions. Following sulfate erosion, concrete expands, cracks, dissolves, peels off, and decreases in strength, which affects the durability of structures. Polypropylene fiber (PP) is widely used in various concrete structures because of its good mechanical properties and chemical corrosion resistance. However, PP fiber has a number of shortcomings, such as a smooth surface, poor hydrophilicity, lack of active groups in the molecular chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…It was also observed that CF had more ridges than PF. This observation is consistent with Hu & Ma, [17] who stated that the PF's surface was smooth. Meanwhile, CF had more groves as stated by Tian et al, [18].…”
Section: Microstructural Properties Of Fibresupporting
confidence: 92%

Engineering Properties of Cement-Paste with Polypropylene and Carbon Fibres

Anand Ryan Thurairajah,
Ahmad Nurfaidhi Rizalman,
Eliezer Nevall Anthony
et al. 2024
ARAM
“…It was also observed that CF had more ridges than PF. This observation is consistent with Hu & Ma, [17] who stated that the PF's surface was smooth. Meanwhile, CF had more groves as stated by Tian et al, [18].…”
Section: Microstructural Properties Of Fibresupporting
confidence: 92%

Engineering Properties of Cement-Paste with Polypropylene and Carbon Fibres

Anand Ryan Thurairajah,
Ahmad Nurfaidhi Rizalman,
Eliezer Nevall Anthony
et al. 2024
ARAM
“…It is conditionally possible to divide the studies conducted by other authors by grouping them into several groups of factors. For example, some authors [12,15,[18][19][20][23][24][25]34,36] were engaged in research aimed at improving the corrosion resistance of cement-based concrete, which are the most traditional type of concrete in current construction but are not environmentally friendly and cheap, leaving a high carbon footprint and not in line with the modern ESG agenda. Other authors [7][8][9][10][11]22,27,29,31,35] were engaged in developing compositions of geopolymer concrete aimed at improving the mechanical properties of such concrete: their strength and improvement of deformation properties.…”
Section: Discussionmentioning
confidence: 99%
“…Five mix ratios were designed in the test, as shown in Table 4. Their polypropylene fiber contents were 0% or 0.6% [30][31][32][33] and their nano-clay contents were 0%, 4%, 6%, and…”
Section: Experiments Schemementioning
confidence: 99%
“…Five mix ratios were designed in the test, as shown in Table 4. Their polypropylene fiber contents were 0% or 0.6% [30][31][32][33] and their nano-clay contents were 0%, 4%, 6%, and 8%. Unconfined compression tests and unconsolidated undrained shear tests were carried out on the five types of specimens.…”
Section: Experiments Schemementioning
confidence: 99%